The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1242/dev.026807
|View full text |Cite
|
Sign up to set email alerts
|

A differential developmental pattern of spinal interneuron apoptosis during synaptogenesis: insights from genetic analyses of the protocadherin-γ gene cluster

Abstract: Although the role of developmental apoptosis in shaping the complement and connectivity of sensory and motoneurons is well documented, the extent to which cell death affects the 13 cardinal classes of spinal interneurons is unclear. Using a series of genetic manipulations in vivo, we demonstrate for the first time a differential pattern of developmental apoptosis in molecularly identified spinal interneuron populations, and implicate the adhesion molecule family encoded by the 22-member protocadherin-γ (Pcdh-γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
236
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(261 citation statements)
references
References 84 publications
23
236
2
Order By: Relevance
“…Moreover, a recent study has shown that mice deficient for ␥-protocadherin molecules experience a loss of ventral interneurons but not of motoneurons. In these animals, there is a 70% loss in the afferent collaterals projecting to ventral interneurons and a 2.5 increase in the area of terminals in the motor nucleus (Prasad et al 2008;Prasad and Weiner 2011). Thus a loss of afferent input to ventral interneurons is accompanied by an increase in the number of inputs to motoneurons.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, a recent study has shown that mice deficient for ␥-protocadherin molecules experience a loss of ventral interneurons but not of motoneurons. In these animals, there is a 70% loss in the afferent collaterals projecting to ventral interneurons and a 2.5 increase in the area of terminals in the motor nucleus (Prasad et al 2008;Prasad and Weiner 2011). Thus a loss of afferent input to ventral interneurons is accompanied by an increase in the number of inputs to motoneurons.…”
Section: Discussionmentioning
confidence: 95%
“…This has important implications for any potential role for γ-Pcdhs in the control of synaptic specificity, which remains to be demonstrated but would be consistent with some (although not all; see ref. 11) extant functional data in vivo (9,10,12,13,46). Several reports indicate that single neurons of the same cell type can express different subsets of clustered Pcdh isoforms (4,8,(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated critical roles for the 22-member γ-Pcdh family in central nervous system development through analysis of mice in which the entire gene cluster has been deleted (5). These null mutants exhibit severe neurologic defects and die shortly after birth, exhibiting severe apoptosis of spinal cord interneurons and concomitant loss of synapses (5,9,10). An increase in neuronal apoptosis is also observed in the postnatal retina (11) and hypothalamus (12) when the γ-Pcdhs are disrupted using a conditional allele.…”
mentioning
confidence: 99%
“…The first role identified for Pcdhg family members is in neuronal survival, as evidenced by the massive apoptosis and eventual loss of spinal interneurons and retinal cells in Pcdhg-deficient mice (Wang et al, 2002b;Weiner et al, 2005;Lefebvre et al, 2008;Prasad et al, 2008). In both the spinal cord and retina, the neuronal loss is accompanied by reduced numbers of synapses, raising the possibility that the loss of Pcdhg proteins may lead to synaptic loss, which in turn compromises neuronal survival.…”
Section: Roles In the Nervous Systemmentioning
confidence: 99%